Synthesis and preliminary evaluation of 18F-labeled 1-(6, 7-dimethyl-4-(methylamino)-1, 3-dihydro-2H-pyrrolo[3, 4-c]pyridin-2-yl)-2-(trans-2-(6-fluoropyridin-3-yl)cyclopropyl)ethan-1-one for imaging muscarinic acetylcholine receptor subtype 4. Issue 27 (2nd July 2020) - Deng, Xiaoyun; Zhang, Yiding; Rong, Jian; Kumata, Katsushi; Shao, Tuo; Wang, Gangqiang; Hatori, Akiko; Mori, Wakana; Yu, Qingzhen; Hu, Kuan; Fujinaga, Masayuki; Shao, Yihan; et al.
Graphical abstract: Highlights: Efficient radiosynthetic route to a 18 F-labeled M4 PET ligand. High radiochemical yield and high molar activity. Modest in vitro binding specificity by autoradiography studies. Limited brain penetration in rodents. Abstract: Positive allosteric modulators of muscarinic acetylcholine receptor subtype 4 have been identified as promising activators for the treatment of neurological disorders and neurodegenerative diseases, including schizophrenia, Alzheimer's disease (AD) and dementia with Lewy bodies (DLB). Herein we report the synthesis and preliminary evaluation of a 18 F-labeled positron emission tomography ligand based on a M4 activator (7 ). 18 F-Isotopologue of 7 was prepared in a reasonable radiochemical yield with high radiochemical purity (>99%) and high molar activity (>37 GBq/µmol). In vitro autoradiography studies indicated that the ligand possessed moderate in vitro specific binding. Dynamic PET studies in vivo demonstrated that [ 18 F]7 (also named as [ 18 F]M4 R-1911) failed to cross the blood–brain barrier. Therefore, further chemical scaffold optimization in chemotype of 7 is necessary to overcome limited brain permeability and improve specific binding.